Concurrent Brucellosis and Q Fever Infection: a Case Control Study in Bamyan Province, Afghanistan - Khwaja Mir Islam Saeed; Jamalludin Ahadi; Mohammad Nadir Sahak; Ahmad Farid Ghiasi; Rana Jawad Ashgar (University Library System, University of Pittsburgh, 2014)
Background: More than 500,000 people are affected by brucellosis each year while the incidence of Q fever is poorly recorded. Consistent outbreaks of brucellosis have been reported in Afghanistan, affecting social and economic life. This study aimed to determine the means of propagation of brucellosis and Q-fever and establish appropriate control measures for both. Methods and Materials: An outbreak of 1,317 cases of brucellosis and Q fever was investigated from May 2011 to the end of 2012 in Bamyan province of Afghanistan.A total of 100 cases were selected by random sampling with equal number of neighbor controls. Data were collected through structured questionnaire. Results: The average age was 30 years ±14 years. Of those sampled, 62% were female, 38% were male, and resided in three districts: Punjab, Yakawlang and Waras. Using multivariate analysis, being a housewife (OR=7.36), being within proximity of kitchens to barns (OR= 2.98), drinking un-boiled milk (OR= 5.26), butchering (OR= 3.53) and purchasing new animals in the last six months (OR= 3.53) were significantly associated with contraction of brucellosis and Q fever. Conclusion: Health educators should focus on families dealing with animals, especially on females. Pasturing, healthy milking, dunging, and slaughtering practices, along with use of safe dairy products should be the focus of preventive measures.